2020
DOI: 10.7150/thno.47317
|View full text |Cite
|
Sign up to set email alerts
|

MR-detectable metabolic biomarkers of response to mutant IDH inhibition in low-grade glioma

Abstract: Mutations in isocitrate dehydrogenase 1 (IDH1mut) are reported in 70-90% of low-grade gliomas and secondary glioblastomas. IDH1mut catalyzes the reduction of α-ketoglutarate (α-KG) to 2-hydroxyglutarate (2-HG), an oncometabolite which drives tumorigenesis. Inhibition of IDH1mut is therefore an emerging therapeutic approach, and inhibitors such as AG-120 and AG-881 have shown promising results in phase 1 and 2 clinical studies. However, detection of response to these therapies prior to changes in tumor growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 59 publications
(137 reference statements)
2
30
1
Order By: Relevance
“…It is also in line with reports in both preclinical and clinical studies [26,33,43]. The changes in 2-HG and Glu levels are also in line with our previous observations in the U87IDHmut cells treated with either AG-120 or AG-881 that showed a significant decrease in 2-HG and a significant increase in Glu [34]. GLX, which is also increased in this in vivo study, reflects the sum of Glu and Gln.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is also in line with reports in both preclinical and clinical studies [26,33,43]. The changes in 2-HG and Glu levels are also in line with our previous observations in the U87IDHmut cells treated with either AG-120 or AG-881 that showed a significant decrease in 2-HG and a significant increase in Glu [34]. GLX, which is also increased in this in vivo study, reflects the sum of Glu and Gln.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that cells genetically engineered to express mutant IDH1 increase 2-HG and also decrease Glu, phosphocholine and lactate [37]. However, our previous study in cells [34], as well as the results from this in vivo study, observe a drop in 2-HG and an increase in Glu following mutant IDH inhibition, but no significant changes in lactate or a consistent increase in choline-containing metabolites. Our findings therefore point to the complexity of the molecular biological and metabolic changes that occur in mutant IDH1 tumors during their development and in response to treatment [46].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Glioma is one of the most common brain tumors 1 , 2 , which is classified into grades I-IV according to the World Health Organization (WHO) 3 . Accumulating evidence suggests that perturbation of gene expression is closely associated with carcinogenesis, which might be triggered by genomic rearrangement 4 , site-specific transcription factors 5 , or long-range enhancer interactions 6 .…”
Section: Introductionmentioning
confidence: 99%